Evaluation of relationship between odontogenic infections and maxillary sinus changes: A Cone Beam Computed Tomography-based study - Suman Bisla; Ambika Gupta; Harneet Singh; Ankita Sehrawat; Shubhangi Shukla (Elsevier, 2022)
Introduction: Odontogenic infections affects the maxillary sinus mucosa. Cone Beam Computed Tomography (CBCT) is helpful in diagnosis of maxillary sinusitis of odontogenic origin. This cross-sectional study was planned with the aim to assess maxillary sinus changes associated with odontogenic infection by evaluating CBCT images. Material and methods: In cross-sectional analytical study, total 213 patients (404 sinuses) were evaluated on CBCT after thorough clinical examination of the individuals and taking into consideration the history of rhino or allergic rhinitis. Based upon CBCT images and clinical examination, patients were divided into, study group (odontogenic infection) and control group (no associated odontogenic infection). Effect of the size of periapical lesion, spatial relationship of lesion to the sinus floor and periodontal bone loss on maxillary sinus changes were evaluated. Results: Mucosal changes found in 200 sinuses (49.5%), mucosal thickening being the most prevalent and more commonly associated with odontogenic infections (p = 0.004). A significantly increased risk of mucosal thickening was observed with severe periodontal bone loss (p = 0.008). Size and spatial relationship of lesion to the maxillary sinus had no impact on the prevalence of mucosal thickening (p = 0.6, p = 0.4 respectively). Periodontal bone loss was 2.2 more likely to be associated with mucosal thickening than periapical or combined lesion. Conclusions: Most prevalent sinus change was mucosal thickening. Periodontal bone loss was significantly associated with mucosal thickening. CBCT is an appropriate method for sinus evaluation.